Korupsi sebagai Kejahatan Kemanusiaan dalam Perspektif Fasad fi al-Ardh dan Hukum Indonesia - Muhammad Lutfi Abdullatif (Yayasan Cendekia Gagayunan Indonesia, 2025)
Corruption in Indonesia is no longer seen as an ordinary crime, but has developed into an extraordinary crime that damages the system and order of national life. A positive legal approach through the Corruption Law is considered to be unable to provide a deterrent effect or touch the root of the problem of substantive justice. This research aims to offer an alternative perspective by positioning corruption as a crime against humanity through the study of the concept of fasad fi al-ardh in the Qur'an. The method used is normative legal research with philosophical, conceptual, and comparative approaches. Primary data is sourced from the Qur'an and laws and regulations, while secondary data comes from books of tafsir, books, and scientific journals. The results of the study show that the characteristics of the fi al-ardh façade, such as massive damage, betrayal of public trust, and dehumanization, have a substantive conformity with systemic corruption practices in Indonesia. This similarity provides a strong philosophical basis for reformulating national criminal law policy. This study proposes: (1) increasing the qualification of systemic corruption as an extraordinary crime equivalent to a crime against humanity; (2) the application of heavier and proportionate punishment as reflected in the QS. Al-Maidah: 33; and (3) strengthening additional restorative punishments, including the allocation of fines for the socio-economic recovery of the community. The findings of this study confirm that the integration of fi al-ardh façade values in national criminal law policy can be a progressive paradigm to strengthen moral legitimacy, law enforcement effectiveness, and eradication of corruption in Indonesia.